Pioglitazone combined with atorvastatin promotes plaque stabilization in a rabbit model. (December 2022) - Zhang, Xuehui; Chen, Xue; Liang, Zhe; Nie, Maoxiao; Yan, Yunfeng; Zhao, Quanming
Objective: It is not yet clear whether plaque inflammation and cardiovascular events are reduced further when pioglitazone and atorvastatin are combined. Our study aimed to determine whether pioglitazone combined with atorvastatin can restrain the progression of atherosclerosis and promote plaque stabilization in a rabbit model Method and Result: Thirty rabbits were randomly divided into an atherosclerosis group, an atorvastatin group, and an atorvastatin plus pioglitazone group. The atherosclerosis model was induced using balloon injury and feeding a high-fat diet. Plasma samples were then used to analyze glucose, triglycerides (TG), high-density lipoprotein-cholesterol (HDL-C), low-density lipoprotein-cholesterol (LDL-C), high-sensitivity C-reactive protein (hs-CRP), and matrix metalloproteinase-9 (MMP-9). The area percentage of atherosclerotic plaques was analyzed by hematoxylin-eosin staining. The relative reductions in TG and LDL-C and the increase in HDL-C levels were significantly greater in the combination therapy group than in the atorvastatin monotherapy group (TG: −33.60 ± 7.17% vs −24.16 ± 8.04%, p < 0.001; LDL-C: −42.89 ± 1.63% vs −37.13 ± 1.35%, p < 0.001; and HDL-C: 25.18 ± 5.53% vs 10.43 ± 6.31%, p < 0.001). The relative reductions in hs-CRP and MMP-9 levels were significantly greater in the combination therapy group than in the atorvastatin monotherapy group (−69.38 ± 1.06% vs-53.73 ± 1.92%, p < 0.001; −32.77 ± 2.49% vs −13.36 ± 1.66%, p < 0.001). The area percentage of atherosclerotic plaques was significantly smaller in the atorvastatin group (47.75%, p < 0.05) and in the atorvastatin plus pioglitazone group (22.57%, p < 0.05) than in the atherosclerosis group (84.08%, p < 0.05) Conclusion: We can thus conclude that the combination treatment of atorvastatin and pioglitazone provided additive benefits on inflammatory parameters and lipid metabolism. Pioglitazone combined with atorvastatin can further restrain the progression of atherosclerosis and promote plaque stabilization in a rabbit model.